HUBUNGAN ANTARA METODE DISKUSI DENGAN KEPERCAYAAN DIRI SISWA DI SDN KUALA LUPAK KABUPATEN BARITO KUALA - Nurul Huda Fitriani (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
This study aims a) to determine the application of the discussion method, b) to determine the level of student self-confidence, and c) to determine the relationship between the discussion method and the self-confidence of students at SDN Kuala Lupak, Barito Kuala Regency. This study uses a correlational method and a means of collecting data is a questionnaire. The research sample used purposive sampling technique with a sample of 39 grade students and class VI students. Based on data analysis, the application of the discussion method in SDN Kuala Lupak, Barito Kuala Regency is quite good with an average value of 45.6. The self-confidence of students at SDN Kuala Lupak, Barito Kuala Regency, is in the medium category with an average score of 62.8. The results of data analysis based on the calculation of the two questionnaires show that the t-count value of 14.847 has exceeded the t-table values, both at the 5% and 1% significant levels. Written: t table (5% = 2,026) <tcount (14,847)> ttable (1% = 2,715). It is concluded that the alternative hypothesis (Ha) which says there is a significant relationship between the discussion method and the students' self-confidence at SDN Kuala Lupak, Barito Kuala Regency is accepted.